Thermal Performance of Ventilated Double Skin Façades with Venetian Blinds - Jordi Parra; Alfredo Guardo; Eduard Egusquiza; Pere Alavedra (Energies, 2015)
Venetian blinds (VB) are shading devices of widespread use in residential and corporate buildings. They can reflect or transmit light into buildings and at the same time allow daylighting and exterior views. They can also efficiently block radiative heat from entering the building, and if combined with a heat dissipation system such as forced ventilation, they can improve the thermal performance of double skin façades (DSF). Computational Fluid Dynamics (CFD) has proven to be a useful tool for modeling flow and heat transfer in DSF, including conduction, convection and radiation heat transfer phenomena. The aim of this work is to evaluate, by means of CFD, the influence of several optical, construction and operation parameters of a DSF (such as optical properties of the materials, geometrical relations of the VB or flow stream conditions) in terms of energy savings, measured as a reduction of the solar load entering the building. Results obtained show that parameters such as the proximity of the VB to the exterior skin of the façade or a differentiated surface treatment for the exterior and interior faces of the VB louvers can notably affect the thermal performance of the DSF and hence the heat gains experienced by the building.